Digital Skills Improvement for MSMEs in Rural Areas for Online Marketing - Febrianty, Yenny; Awaludin, Dipa Teruna; Safar, Muh.; Kraugusteeliana, Kraugusteeliana; Suseno, Suseno (Unram Journal of Community Service, 2024)
This Community Service (PKM) aims to improve the digital skills of MSME actors in rural areas, especially in online marketing, through online training using the Zoom platform. This activity is motivated by the low digital skills of MSMEs in rural areas, which limits their access to the digital market. The method used is participatory action research (PAR), involving 30 MSME actors who are selected by purposive sampling. The training lasts four weeks and includes two weekly sessions, covering material on digital marketing, the use of social media, e-commerce, and marketing performance monitoring. The results showed a significant improvement in participants' digital skills, with an average pre-test score of 45 increasing to 80 on the post-test. Implementing the skills learned also resulted in an increase in engagement on social media by 40% and an increase in online transactions by 20%-30%. Participants gave positive feedback regarding the relevance of the training and the application of the skills taught. This activity fills the gap in previous research by focusing on practical strategies adapted to the conditions of MSMEs in rural areas. The main obstacle faced is the problem of internet connectivity, which needs to be considered in the next training. Overall, this activity has succeeded in increasing the competitiveness of MSMEs in the digital market